Pengaruh variasi konsentrasi pelarut, waktu, dan suhu destilasi terhadap total fenol ekstrak daun sereh wangi (Cymbopogon winterianus Jowwit) - Ike Sitoresmi Mulyo Purbowati; Ali Maksum; Gunawan Wijonarko (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The citronella plant (Cymbopogon winterianus Jowwit) has been known to have phenolic compounds that have the potential as antioxidants. The more phenolic compounds extracted, the better the quality of the extract obtained. To obtain maximum total phenol levels, extraction treatment was carried out with variations in time, temperature, and solvent concentration to extract fragrant Citronella leaves. This study aimed to determine the right time, temperature, and solvent concentration to obtain citronella extract with maximum total phenol content. Extraction was carried out by water distillation technique using ethanol solvent with concentration variations of 40%, 50%, 60%, 70%, 80%, and 90% with time variations of 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and temperature variations extraction, namely 50, 60, 70, and 80oC, The total phenol content of citronella extract was analyzed using a UV-VIS spectrophotometer based on the reduction reaction of the Folin-Ciocalteu reagent. The results showed that the extract with the highest total phenol content was 7.075 with a time of 4 hours, a temperature of 80 C, and using a solvent concentration of 90%. Characteristics produced from citronella extract with the highest phenol content, namely total flavonoids at 41.75 mgQE/g, antioxidant activity at 11.242 ppm, antibacterial activity at E. coli is 10.2 mm and in S. aureus is 12.7 mm. This research is expected to have an impact on the exploration of the extraction of bioactive compounds in citronella plants.